Oral history sessions at the Centro de Textiles del Mundo Maya: making the voice of the weavers present in cultural narratives - Ojinaga Zapata, Brenda Cecilia (SCT Proceedings in Interdisciplinary Insights and Innovations, 2024)
Traditional textiles have been a fundamental tool for the construction of the collective memory of some weaving communities. However, when studying the textile collections of the Mayan World Textile Center, located in the Chiapas Highlands, Mexico, I was confronted, over several years, with the omission of the stories and voices of their creators, who were called again and again: “anonymous author”, so that among the threads and weaves of the textiles, there are stories that often remain hidden.This Textile Center, which is constantly recognized as a ”living center” bearer of a “living art”, discursively appeals to differentiate itself from the ethnographic and anthropological content with which textiles have historically been studied, as well as to point out the incorporation of the weavers into these spaces, who work as room custodians or give weaving demonstrations for the public, and on a few occasions, have taken the space to tell their stories about textiles in oral history sessions.This paper presents some reflections on the importance of orality as a source of knowledge in textile art museums as a means of moving towards a more complete knowledge, which takes the voices and stories of women creators as a starting point. I propose that knowing the testimony of the weavers is fundamental for the work of collective memory and the construction of narratives that are not only more complete, but also fairer.